How Corporate Social Responsibility Engagement Strategy Moderates the CSR–Financial Performance Relationship - Tang, Zhi; Hull, Clyde Eiríkur; Rothenberg, Sandra (Journal of Management Studies, 2012)
abstractWe propose that firm profits are shaped by how firms engage in corporate social responsibility. Recent research on the corporate social responsibility (CSR)–corporate financial performance (CFP) relationship proposes a variety of contextual and organizational factors to create a more robust link. However, few of these studies explore the role of the CSR engagement strategy. Drawing on absorptive capacity theory and related perspectives such as time compression diseconomies, asset mass efficiencies, and path dependence theory, we argue that when a firm engages in CSR slowly and consistently, focuses on related CSR dimensions, and starts with internal dimensions of CSR, CFP will be enhanced. With longitudinal data collected from 130 firms from 1995 to 2007, we find that firms benefit more when they adopt a CSR engagement strategy that is consistent, involves related dimensions of CSR, and begins with aspects of CSR that are more internal to the firm. The pace of the CSR engagement strategy, however, does not moderate the CSR–CFP relationship. This study helps fill the gap in CSR research by showing that, regardless of contextual factors, a firm can choose the proper strategy to enhance the financial benefits of the CSR engagement.